Modernization, cultural change, and democracy: The human development sequence - Inglehart, Ronald (Cambridge University, 2013)
This book demonstrates that people's basic values and beliefs are changing, in ways that affect their political, sexual, economic, and religious behavior. These changes are roughly predictable: to a large extent, they can be explained by the revised version of modernization theory presented here. Drawing on a massive body of evidence from societies containing 85 percent of the world's population, the authors demonstrate that modernization is a process of human development, in which economic development gives rise to cultural changes that make individual autonomy, gender equality, and democracy increasingly likely. The authors present a model of social change that predicts how value systems are likely to evolve in coming decades. They demonstrate that mass values play a crucial role in the emergence and flourishing of democratic institutions